Multistability and switching dynamics in vascular networks - Atkinson, GW (2023)
The formation of regions of low oxygen concentration, or hypoxia, within tumours is a hallmark of many types of cancer. Oxygen starvation of cancerous cells within tumours creates an environment that causes tumours to become more aggressive and more resistant to treatment. Hypoxia within tumours is described as chronic or cycling. Chronic-hypoxia describes permanently hypoxic regions of tissue, and cycling-hypoxia describes short term fluctuations of hypoxia. Counterintuitively, the short term application of oxygen to hypoxic regions does not reverse the negative impact of hypoxia and in many cases exacerbates the negative health impacts associated with hypoxia. A recent hypothesis for the formation of chronic-hypoxia based on the equilibria of steady-state models of blood flow in vasculature networks has been computationally verified. Blood flow within the vasculature dictates the distribution of RBCs (Red Blood Cells) within a tumour, and if the distribution of RBCs for a blood flow equilibrium is asymmetric and uneven, then the tissue surrounding vessels with fewer RBCs suffers hypoxia.